2002
DOI: 10.4049/jimmunol.168.1.240
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Variation in Human and Common Chimpanzee CD94 and NKG2 Genes

Abstract: To assess polymorphism and variation in human and chimpanzee NK complex genes, we determined the coding-region sequences for CD94 and NKG2A, C, D, E, and F from several human (Homo sapiens) donors and common chimpanzees (Pan troglodytes). CD94 is highly conserved, while the NKG2 genes exhibit some polymorphism. For all the genes, alternative mRNA splicing variants were frequent among the clones obtained by RT-PCR. Alternative splicing acts similarly in human and chimpanzee to produce the CD94B variant from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 71 publications
4
78
2
Order By: Relevance
“…23 An example of NKG2D PCR-SSP typing is shown in Figure 2c. The results of the NKG2D reactions were confirmed by the direct sequencing of genomic DNA from two representative samples for each possible genotype detected (i.e.…”
Section: Primer Designmentioning
confidence: 99%
See 1 more Smart Citation
“…23 An example of NKG2D PCR-SSP typing is shown in Figure 2c. The results of the NKG2D reactions were confirmed by the direct sequencing of genomic DNA from two representative samples for each possible genotype detected (i.e.…”
Section: Primer Designmentioning
confidence: 99%
“…Investigations into the possible influence of MIC polymorphism in celiac disease, a gluten-sensitive enteropathy, suggest a causal role, [16][17][18] although similar studies of IBD have produced conflicting results. [19][20][21][22] In contrast to the MIC genes, NKG2D displays limited polymorphism 23 and has not previously been investigated in susceptibility to UC.…”
Section: Introductionmentioning
confidence: 99%
“…The KIR family is important in humans and other primates, having undergone extensive diversification under positive selection. In contrast, the CD94-NKG2A system has remained relatively well conserved across the species with orthologous genes in primates and a closely related functional homolog in rodents (3,4). Consistent with the coevolution of these families and their MHC class I ligands, KIR bind polymorphic MHC class I, HLA-A, -B, and -C molecules, whereas CD94-NKG2A binds the conserved oligomorphic HLA-E molecule or the rodent homolog Qa-1 (5,6).…”
mentioning
confidence: 96%
“…The CD94 and NKG2D genes are monomorphic in the primate species tested, except for the orangutan where polymorphisms have been reported for the CD94 gene [60]. For the activating receptor genes NKG2C allelic polymorphism have been identified in primates [61][62][63]. Although the general genomic organisation of the CD94 to LY49L interval appears to be conserved in primates, particularly the activating receptor genes appear to be subject of duplications (Fig.…”
Section: Receptors Of Nk Cellsmentioning
confidence: 99%
“…2). For example the chimpanzee NKG2C gene is duplicated [62] and in rhesus macaques, NKG2C is at least duplicated (own unpublished data) and several sequences have been identified that appear to be derived from duplications of the NKG2F locus [61,64]. In the orangutan, a gene has been identified that is equally related to human NKG2C and NKG2E and is thus designated NKG2CE [60].…”
Section: Receptors Of Nk Cellsmentioning
confidence: 99%